Modified perineal urethrostomy for the management of congenital urethral diverticulum in a 4-month-old feline - Paloma Helena Sanches da Silva; Mariana Zanini Maia; Barbara Vidal Barbosa; Pedro Antônio Bronhara Pimentel; Juliana dos Santos Masiero; Suzane Lilian Beier; Patrícia Maria Coletto Freitas (Ciência Rural)
ABSTRACT: A male, intact, four-month-old feline was referred for veterinary evaluation due to persistent episodes of urinary incontinence that began two months prior, along with a protrusion under the skin in the perineal region. The patient was presumptively treated for cystitis but continued to experience recurrent episodes of urinary incontinence. Following a retrograde contrast urethrocystography and urine collection through guided puncture of the protrusion, a suspicion of urethral diverticulum arose. Therefore, the treatment option was to perform a modified technique of perineal urethrostomy using the diverticulum in the pelvic urethra, through both abdominal and perineal surgical approaches. Two months post-surgery, the patient no longer exhibited clinical signs of urinary incontinence. The modified perineal urethrostomy technique proved to be a viable treatment option for young cats with urethral diverticulum. This is the third case reported in the veterinary literature of a young feline patient with suspected urethral diverticulum that successfully responded to surgical treatment with perineal urethrostomy.